IMPLEMENTASI PROGRAM PENDIDIKAN INKLUSIF DI SMP NEGERI 29 SURABAYA - NURITA FEBRIYANTI (Publika, 2014)
ABSTRACT The inclusive education is a program which is controled by East Java Governor Regulation Number 6 Year 2011 about Inklusif Education. Inklusif education is organization of education systems which gives chance to all students with special needs. So they can following education or learning in the education zona together with another normal students. In implementation of education inklusif program in SMP Negeri 29 Surabaya. There is found some problems namely teachers with special counselos less, the unavailability of education social workers, unavailability of the rapist. Thus the purpose of this study is to describe the implementation of inclusive education programs in the SMP Negeri 29 Surabaya. This type of research is descriptive study with a qualitative approach. Location of the study in the SMP Negeri 29 Surabaya is the first school to implement inclusive education program. The focus of the research is implementation of inclusive education programs by using the theory Merile S. Grindle. Data collection techniques used were interviews, observation, documentation, and triangulation. Based on the results of research, implementation of inclusive education programs seen from variable content of policy, East Java Governor Regulation Number 6 Year 2011 meet all the interests of learners with special needs, benefits provided by the program felt by all children with special needs, target changes from east java governor regulation has been reached, the location of decision-making is appropriate, policy implementor it is clear and precise, human resources for special teachers less team, education social workers and team therapist not yet allocated, non-human resources already fulfilled. While the views of the variable implementation environment, all problem is bellow control of Dinas Pendidikan dan Kebudayaan Kota Surabaya, interests of the actors invoived similarities showed that to succeed in the implementation of inclusive education, the strategy adopted is right, the characteristics and the regime can create an educational environment that does not discriminate and compliance with the target group is very high in inclusive education activities in schools can streamlining the process of implementation of inclusive education in the SMP Negeri 29 Surabaya. Based on the resuits of research, advice given researchers that it is expected that the policy implementers keep doing coaching or training to educators to add insight and knowledge regarding the implementation of inclusive education, continue to socialize to the community related to the implementation of inclusive education it can be seen and felt by all children with special needs, it should be added again special teachers as well as the necessary allocation education social workers and energy therapist for the implementation of inclusive education in the SMP Negeri 29 Surabaya. Keyword : Policy Implementation, Inclusive Education Program ABSTRAK Pendidikan inklusif merupakan sebuah program yang diatur dalam Peraturan Gubernur Jawa Timur Nomor 6 Tahun 2011 tentang Penyelenggaraan Pendidikan Inklusif. Pendidikan inklusif adalah sistem penyelenggaraan pendidikan yang memberikan kesempatan kepada semua peserta didik berkebutuhan khusus untuk dapat mengikuti pendidikan atau pembelajaran dalam lingkungan pendidikan secara bersama-sama dengan peserta didik pada umumnya. Dalam mengimplementasikan program pendidikan inklusif di SMP Negeri 29 Surabaya, ditemukan beberapa masalah yaitu kurangnya tenaga guru pembimbing khusus, tidak tersedianya tenaga pekerja sosial pendidikan, tidak tersedianya tenaga terapis. Maka dari itu tujuan penelitian ini adalah untuk mendeskripsikan implementasi program pendidikan inklusif di SMP Negeri 29 Surabaya. Jenis penelitian yang digunakan adalah penelitian deskriptif dengan pendekatan kualitatif. Lokasi penelitian di SMP negeri 29 Surabaya karena sekolah tersebut merupakan sekolah pertama yang mengimplementasikan program pendidikan inklusif. Fokus penelitian adalah implementasi program pendidikan inklusif dengan menggunakan teori Merile S. Grindle. Teknik pengumpulan data yang digunakan adalah wawancara, observasi, dokumentasi dan triangulasi. Berdasarkan hasil penelitian, implementasi program pendidikan inklusif dilihat dari variabel isi kebijakan, Peraturan Gubernur Jawa Timur Nomor 6 Tahun 2011 memenuhi semua kepentingan peserta didik anak berkebutuhan khusus, manfaat yang diberikan dengan adanya program tersebut dirasakan oleh semua anak berkebutuhan khusus, target perubahan dari Peraturan Gubernur Jawa Timur sudah tercapai, letak pengambilan keputusan sudah tepat, implementor kebijakan sudah jelas dan tepat, sumber daya manusia untuk tenaga guru pembimbing khusus kurang, tenaga pekerja sosial pendidikan dan tenaga terapis belum dialokasikan, sumber daya non-manusia sudah terpenuhi. Sedangkan dilihat dari variabel lingkungan implementasi, kekuasaan sepenuhnya ada pada Dinas Pendidikan dan Kebudayaan Kota Surabaya, kepentingan para aktor yang terlibat menunjukkan kesamaan yaitu untuk mensukseskan penyelenggaraan pendidikan inklusif, strategi yang diterapkan sudah tepat, karakteristik dan rezim yang berkuasa dapat menciptakan lingkungan pendidikan yang tidak diskriminasi, dan kepatuhan target group yang sangat tinggi dalam kegiatan pendidikan inklusif di sekolah dapat memperlancar proses implementasi program pendidikan inklusif di SMP Negeri 29 Surabaya. Berdasarkan hasil penelitian, saran yang diberikan peneliti yaitu diharapkan para pelaksana kebijakan terus melakukan pembinaan atau pelatihan kepada pendidik mengenai penyelenggaraan pendidikan inklusif, terus melakukan sosialisasi kepada masyarakat tertakait penyelenggaraan pendidikan inklusif, perlu ditambah lagi tenaga guru pembimbing khusus serta perlu dialokasikannya tenaga pekerja sosial pendidikan dan tenaga terapis untuk penyelenggaraan pendidikan inklusif di SMP Negeri 29 Surabaya. Kata Kunci : Implementasi Kebijakan, Program Pendidikan Inklusif